PENGARUH PRAKTIK AKUNTANSI DENGAN PRINSIP KEHATI-HATIAN (PRUDENTIAL PRINCIPLE) TERHADAP KUALITAS LABA DAN TINGKAT PENGEMBALIAN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Ana Septiani (Universitas Muhammadiyah Metro, 2017)
Abstract The financial statements provide information that contains performance and financial position of a company. The financial statements conform to the principles of accounting in accordance with generally accepted standards to be useful to users in decision making of economic. The financial statements that are useful are the financial statements of good quality and can be an indicator for future earnings in order to maximize the stock return and optimize the benefits for all stakeholders.This research is quantitative. The purpose of this study was to obtain empirical evidence about the effect of accounting practices with the prudential principle on the quality of earnings and stock returns. Variable measurement using indicators that are adapted to journal the adoption of this research that Penman and Zhang (2002), among others subscore consisting of inventory reserve, research and development reserves and advertising reserves, used to measure the accounting practices with the prudential principle, Qscore used to measure quality earnings and returns are used to measure stock returns. The population in this study are all companies listed on the Indonesia Stock Exchange period 2012 to 2014. The sample period is a manufacturing company that has made the convergence of IFRS. Total sample was 84 manufacturing company's financial statements every period of observation so that the total samples analyzed were as 252 manufacturing company financial statements for three periods of observation. Data analysis was performed with the classical assumption and hypothesis testing with multiple linear regression analysis. Statistical program in this study using SPSS 22. The results showed that subscore is the inventory reserves, research and development reserves and advertising reserves on accounting practices with the prudential principle to produce earnings quality is good, besides the results also showed that the stock market can